Effects of MnTBAP on Porcine Semen Cryopreservation and Capacitation - Eunji Kim; Il-Jeoung Yu; Joohyeong Lee; Yubyeol Jeon (MDPI AG, 2024)
Antioxidants protect cellular function and structure by neutralizing the oxidative stress caused by increased reactive oxygen species (ROS) during sperm freezing. Studies on cryopreservation using various antioxidants have demonstrated encouraging results. Many studies have used antioxidants to increase the efficiency of sperm freezing and to improve the success rate of artificial insemination and pregnancy. Manganese (III) tetrakis (4-benzoic acid) porphyrin chloride (MnTBAP) is a newly synthesized antioxidant with positive effects on sperm morphology and capacitation in humans, rams, and stallions. In this study, porcine semen was treated with 0, 50, 100, and 150 μM of MnTBAP based on a Tris-egg-yolk extender and frozen to determine whether MnTBAP can assist the status of sperm during cryopreservation. First, motility was assessed using the computer-assisted sperm analysis (CASA) system, with the 100 μM treatment group showing the highest motile rate (66.8%) compared with that of the other groups (control, 51.1%; 50 μM and 150 μM, 59.6%); therefore, the remaining analyses were conducted comparing the two groups (control vs. 100 μM group; p < 0.01). Second, fluorescence staining was applied to examine the control and 100 μM groups using fluorescence microscopy. The viability (41.7% vs. 62.4%) and the acrosome integrity (77.9% vs. 86.4%) differed significantly (p < 0.05). In addition, the mitochondrial membrane potential (MMP) was 46.5% vs. 51.9%; the fragmentation rate, estimated using the Sperm-sus-Halomax kit, was 63.4% vs. 57.4%; and the detected caspase activity was 30.1% vs. 22.9%. These tended to be higher in the treated group but did not differ significantly. Third, measurements using FACSLyric revealed that the 100 μM treatment group exhibited a state of elevated normal lipid arrangement within the plasma membrane and diminished levels of apoptosis and ROS (p < 0.01). We assessed the expression of genes relevant to antioxidant effectiveness using real-time RT-qPCR. Our findings indicated significant alterations in the expression levels of various mRNA species, with the exception of NOX5 (p < 0.05). Finally, the straws were dissolved and used to treat matured denuded oocytes to investigate the effect on fertilization and embryo development in vitro. The cleavage rate was (77.6% vs. 84.1%), and the blastocyst rate was 9.7% vs. 11.4% (p < 0.05). In conclusion, these results suggest that MnTBAP positively affected sperm freeze-thawing, improving the fertilization capacity, and leading to increased embryo development.